Особливості фільтрування суспензії спіруліни - Голодний, І. М . (Енергетика і автоматика, 2017)
UDC 542.6:639.6.64FEATURES FILTERING THE SLURRY SPIRULINAI. Golodnyi Suspension - a homogeneous liquid multiphase system that is characterized by grain size of the dispersed phase:- Rough suspension - particle size more than 100 microns;- Thin slurry - 0.5 ... 100 microns;- Muti - 0.1 ... 0.5 microns;- Colloidal solutions - less than 0.1 microns.The suspension applies to spirulina fine suspensions in which the size of solid particles (cells spirulina) have a size 6 ... 8 microns.Aim of paper - reduce energy costs in obtaining concentrated algal nutrients.Materials and research methods. Investigation of spirulina suspension conducted using the theory and practice of separation sispenziyi and computer statistical analysis of experimental data.Materials and research methods. The suspension is characterized by weight ratio of liquid and solid phases (P:T). In the slurry phase dispersive spirulina serving nutrient solution and dispersed - cells of the algae. The nutrient solution is dissolved salts. The total amount of dissolved salts in one liter of water is called salinity in grams, is determined washed and designated S, 0/00. Investigation of physical and mechanical properties were carried out on standard culture medium Zarruka salinity which is S = 22,4 0/00.Density of the dispersed phase (solid) in the study were determined experimentally. Spirulina is dried and compressed into tablets. Five tablets were weighed on technical scales and determine their linear dimensions - diameter and height. Density absolutely dry compressed Spirulina is rtv = 1061.736 kg / m3. This uncertainty of research results is less than 1%.The results of studies of physical and mechanical properties of spirulina suspension and some reference data suspensions are given in the table.Filter - a process of separation of heterogeneous systems by means of porous walls, which holds one phase of these systems and lets others. Based on the research results at a constant pressure difference is established that there are three types of filter clogging pores, which are characterized by different patterns:- Filter clogging every pore of one solid particle;- Filtering the gradual clogging the pores of a few solid particles;- Filtering the intermediate species.The most common and shows quite clearly the type of filtering gradual clogging of pores by many solid particles. This type of filter and suspension include spirulina.Industrial filters distributed by the modes of filters on periodic and continuous, and the value of working pressure - on vacuum filters and filters, which work under pressure. Given the fact that the cells of spirulina collapse under high pressure, the further studies filters, which work under pressure are not considered.When choosing a filter of the following factors:a) the purpose of the filtering process - getting only a security deposit or only filtrate or simultaneously receiving sludge and leach ate for the next vykorylast one;b) the properties of slurry and sludge;c) the other conditions of the process - the scale of production, ease of maintenance, the cost of installation, maintenance and others.To separate suspensions spirulina best suited continuous belt filters, which achieved a clear separation of precipitate and filtrate low concentration suspensions.Research spirulina suspension filtering process carried out at the laboratory bench, which is made in the form of a tray 50´50´40 cm. The bottom tray made of filter material which was tissue of eye size 100¼115 microns. To maintain a constant level of slurry in the tray (constant pressure on the filtering septum) suspension accumulated in the container, which, as the fluid passing through the filter, lodged in the tray.The values that are filtering into the equation are divided into fixed and variable. In all cases, the variables are the amount of leach ate and filtering, constant - resistance of the filter walls and the initial rate of filtration. In a practical sense of constant values necessary to determine the performance of the filter installation, which is designed to separate the suspension with desired properties, in this case suspension of spirulina.Filter spirulina was carried out as follows. In the filter tray served the suspension, which maintained a constant level of slurry at a height of 30 cm. At intervals measured amount of the resulting filtrate volume. Two hours later, passing the filtrate practically stopped. According to research based dependency t/q = f(t), which is a straight line, confirming the previous assumption that the process of filtering suspensions Spirulina is a gradual clogging pores.The resulting direct inclined to the horizontal axis at an angle whose tangent k¢/2 = 6.65 m-1, and cuts on the vertical axis segment 1/Wpoch = 180 m/s. It k¢ = 13,3 m-1 and Wpoch = 0.0056 m/s.From the graph shows that the average rate of filtration decreases rapidly at the beginning of the process, which requires large filter walls and its frequent cleaning.ConclusionsSpirulina suspension and low concentration refers to thin suspensions. A clear separation of precipitate and filtrate reached such suspensions on continuous belt filter installations.It was established that the filter walls of the eye 100¼115 micron filtration initial rate equal to 0.0056 m/s, the coefficient of proportionality - 13.3 m-1. Filtering is a gradual clogging of filter pore walls.